Hypnoteaching Method in Arabic Learning - Baroroh, R Umi; Amrulloh, Abdul Kahfi (Universitas Islam Negeri Raden Intan Lampung, 2019)
Hypnoteaching is a new learning method in Arabic learning. Various kinds of Arabic language learning methods have developed before, such as the lecture method, memorizing vocabulary and Arabic rules. But the method makes students feel bored in learning because it cannot make students enjoy learning so that learning outcomes are better. Starting from the development of hypnoteraphy in various functions and uses such as health, psychological to the world of education which is then called hypnoteaching. This method is a new learning method in Arabic that uses students 'positive suggestions to reach students' subconscious. This innovation is an acute hypnoteraphy with teaching so as to produce a new method as an alternative choice in the selection of fun Arabic learning methods. This research is a library research that seeks to find the literature that is in accordance with the theme of the discussion then analyzed by descriptive analysis. The results showed that hypnoteaching fulfilled the requirements as a new method in Arabic learning. This is one of the innovations in Arabic learning methods that can be used today. Because this method maximizes students' subconscious, so learning can achieve maximum results with fun learning.